Investigation on Interfacial Bonding Characteristics of Steel/Aluminum Bi-Metal Gears by Hot Forging Processing - Zhenghua Meng; Xiangyang Jia; Wei Feng; Wuhao Zhuang; Min Wu (Metals, 2022)
In this study, steel/aluminum bimetal gears were manufactured under different deformation degrees by using hot forging processing. Optical microscope (OM), scanning electron microscopy (SEM) and energy disperse spectroscopy (EDS) were used to observe morphologies and the element composition of the interface region of the bimetal gears with different deformation degrees. Results show that the interface region between steel and aluminum is of mechanical bonding characteristics when the deformation degree is 50% and 70%, and the steel–aluminum interface joining zone is of the metallurgical bonding feature when the deformation degree is 90%. Finite element (FE) simulation of the hot forging process of the bimetal gear was carried out by using DEFORM-3D software. The simulation results show that the increase in the difference between the interfacial radial stress and the flow stress of the steel helps to form metallurgical bonding at the steel–aluminum joining zone.